2023
DOI: 10.1128/spectrum.03615-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Nonpharmaceutical Interventions on Pneumococcal Carriage Prevalence and Density in Vietnam

Abstract: The pneumococcus is a major cause of mortality globally. Implementation of NPIs during the COVID-19 pandemic led to reductions in invasive pneumococcal disease in many countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, incorporating a mechanism of reduced risk for developing an IPD due to the absence of circulation of common respiratory viruses led to similar estimates of the relative reduction in IPD incidence as reported in the EU/EEA for 2020 (Brueggemann et al, 2021; European Centre for Disease Prevention and Control and World Health Organization, 2022). This finding, coupled with the outcome of other studies that found a generally stable pneumococcal carriage prevalence in healthy individuals, both children and adults, during COVID-19 containment measures (Nation et al, 2023; Petrović et al, 2022; Rybak et al, 2022; Willen et al, 2022; Wyllie et al, 2023), supports the alternative hypothesis. This explanation accounts for the decreased incidence of IPD, rather than attributing it to reduced pneumococcal transmission, which resulted in a significant reduction in carriage according to the simulations (Smith and Opatowski, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, incorporating a mechanism of reduced risk for developing an IPD due to the absence of circulation of common respiratory viruses led to similar estimates of the relative reduction in IPD incidence as reported in the EU/EEA for 2020 (Brueggemann et al, 2021; European Centre for Disease Prevention and Control and World Health Organization, 2022). This finding, coupled with the outcome of other studies that found a generally stable pneumococcal carriage prevalence in healthy individuals, both children and adults, during COVID-19 containment measures (Nation et al, 2023; Petrović et al, 2022; Rybak et al, 2022; Willen et al, 2022; Wyllie et al, 2023), supports the alternative hypothesis. This explanation accounts for the decreased incidence of IPD, rather than attributing it to reduced pneumococcal transmission, which resulted in a significant reduction in carriage according to the simulations (Smith and Opatowski, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…This explanation accounts for the decreased incidence of IPD, rather than attributing it to reduced pneumococcal transmission, which resulted in a significant reduction in carriage according to the simulations (Smith and Opatowski, 2021). Furthermore, a study in Vietnam found that reductions in IPD associated with NPIs may be due to reductions in overall pneumococcal carriage density rather than carriage prevalence, driven by reductions in capsular pneumococcal carriage density frequently implicated in IPD (Nation et al, 2023). Considering that common respiratory viruses such as influenza increase pneumococcal carriage density, which contributes to transmission and disease, this hypothesis seems plausible (Alpkvist et al, 2015; Diavatopoulos et al, 2010; McCullers et al, 2010; Short et al, 2012; Wolter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet over the same time period, intriguingly, emerging data report persistent carriage of S . pneumoniae in the community across countries and age groups [ 44 46 ]. It has been suggested that reduced incidence of bacterial infection may thus be explained at least in part by concomitant prevention of other respiratory viruses like influenza [ 47 ], which have been shown to favour progression from bacterial colonization to disease [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. Mice were euthanized at 6 days post co-infection for bacterial burden calculation in the nasal lavage (left) and blood [ 46 ]. Data were calculated as number of colony forming units (CFU) of Spn in nasal lavage and CFU/mL of blood (Data were log10 transformed, and values equal to 0 were regarded as undetectable).…”
Section: Resultsmentioning
confidence: 99%